Protest an power in black Africa. Ed. by R.I. Rotberg and A.A. Mazrui. [With contribs of A. Atmore, R.D. Jackson, Y. Person a.o.] (Oxford University Press, 1970)
With bibliogr., index and maps. Written under the auspices of the Center for International Affairs, Harvard University.